Social Distancing: Prevalence of Depressive, Anxiety, and Stress Symptoms Among Brazilian Students During the COVID-19 Pandemic - Esteves, Cristiane Silva; Oliveira, Camila Rosa de; Argimon, Irani Iracema de Lima (Frontiers in Public Health, 2021)
Social distancing due to the COVID-19 pandemic can impact mental health, triggering symptoms such as anxiety, stress and depression. Therefore, this study aimed to assess the levels of anxiety, depression and stress during the period of social distancing due to COVID-19 in students from a campus of the Federal Institute in the metropolitan area of Porto Alegre/RS. A correlational and exploratory study was performed. The sample of the present research was composed by 208 students, who responded to a self-administered online questionnaire with sociodemographic variables and the Depression, Anxiety and Stress Scale Short Form – DASS-21. The detected prevalence of symptoms classified as moderate-severe was 49% for stress, 39% for depression and 33% for anxiety. An association was found between higher levels of anxiety symptoms (OR = 5.652; 95% CI = 2.872–11.123; p < 0.001), depression (OR = 3.289; 95% CI = 1.810–5.978; p < 0.001) and stress (OR = 5.684; 95% CI = 3.120–10.355; p < 0.001) with occurrence of sleep problems during the period of social distancing. There was a protective factor provided by regular physical exercise in relation to depressive symptoms (OR = 0.490; 95% CI = 0.250–0.960; p =0.033). These data are extremely important for understanding the adverse effect on the mental health of students and for developing psychological support strategies, thus promoting well-being during and after the pandemic.